Beyond Fines: Innovative Corporate Sentences Under Federal Sentencing Guidelines - Richard S. Gruner (Washington University Law Quarterly, 1993)
This Article examines innovative corporate sentences beyond fines. It emphasizes types of corporate sentences recommended under the United States Sentencing Commission's Sentencing Guidelines for Organizations. The Article has four goals. First, it seeks to inform judges, prosecutors, defense attorneys and others in the criminal justice community about these as yet unfamiliar corporate sentencing options. Second, it explores the policy rationales supporting innovative corporate sentences. Third, it considers ambiguities in the Guidelines authorizing innovative corporate sentences and suggests means to resolve these ambiguities. Fourth, the Article articulates principles for sentencing courts to use in crafting specific corporate sentences within the broad authorizing language of the Sentencing Guidelines. Finally, the Article identifies circumstances warranting innovative sanctions under the Guidelines, some limitations on their use, and sentencing and prosecutorial strategies that will maximize public benefits from these sanctions.
Keywords: Criminal liability of juristic persons; Sentencing guidelines (Criminal procedure)